POTENSI AIR TANAH DI DAERAH CIKARANG DAN SEKITARNYA, KABUPATEN BEKASI BERDASARKAN ANALISIS PENGUKURAN GEOLISTRIK - Naryanto, Heru Sri (Jurnal Air Indonesia, 2008)
Groundwater is one of the most important for human activities. The effects of land use and population changes in Bekasi area cause the degradation of groundwater quantity and quality. The aquifers potential in Cikarang and its surrounding as a study area are studied using geoelectric method. Geoelectric analysis can be measured the geometry of subsurface aquifer (thickness, depth, distribution, and structural geology). The aquifers in the study area are included of Bekasi Groundwater Basin System. The aquifers contain confined aquifer and unconfined aquifer. The thickness of unconfined aquifers less than 30 m, as lenses and bottom depth less than 40 m below of land surface. The thickness of confined aquifers is variation with maximum 80 m and the bottom depth 20-160 m below of land surface. The degradation of groundwater in Cikarang and its surrounding needs better groundwater management for sustainable development. Katakunci : potensi airtanah, akuifer, geolistrik, Cikarang